Benefits of a Juvenile Arthritis Support Program (JASP-1) for children recently diagnosed with Juvenile Idiopathic Arthritis and their parents - Karina Mördrup; Johanna Granhagen Jungner; Eva Broström; Karin Palmblad; Cecilia Bartholdson (BMC Rheumatology)
Abstract Background Medical treatment for children with Juvenile Idiopathic Arthritis (JIA) has improved radically since the development of biological disease-modifying antirheumatic drugs. However, children suffer from pain and anxiety, and parents often experience loneliness and lack of support. Some parents reported that information provided at the time their child was diagnosed could be difficult to assimilate. Therefore, the aim of this study was to develop a Juvenile Arthritis Support Program (JASP-1) for children recently diagnosed with JIA and their parents. Moreover, the aim was to explore patients´ and parents´ experiences with JASP-1 and its potential impact on patients´ physical health. Methods JASP-1 included seven patient- and family-centered clinical visit from time of diagnose and one year ahead. Data were collected from a study-specific questionnaire answered by children and their parents after participation in JASP-1 and from the pediatric rheumatology register. The study-specific questionnaire explored participants´ experience with the care they received during their first year with JIA. Registry and questionnaire data from the intervention (JASP-1) group was compared to a control group. Results The analysis revealed that children and parents who completed JASP-1 were more satisfied with the care they had received during their first year with JIA than the control group. The results also showed that children who completed JASP-1 were assessed as having better overall health after 12 months, than children in the control group (JASP-1 = mean 4.33, 95% Confidence Interval (CI) 4.17 − 4.46), (Control = mean 3.68, 95% CI 3.29 − 4.06), (p = 0.002). Moreover, children in the JASP-1 group had less disease impact on daily life (JASP-1 = mean 0.15, 95% CI 0.07 − 0.24) (Control = mean 0.40, 95% CI 0.13 − 0.67), (p = 0.017) and less active joints than the control group (JASP-1 = mean 0.62, 95% CI 0.35 − 1.58), (Control = mean 0.87, 95% CI 0.18 − 1.56), (p = 0.054). Conclusion A support program like JASP-1 could be an effective way of not only supporting children newly diagnosed with JIA and their parents psychologically but may also increase children’s overall physical health and improve quality of care within pediatric rheumatology. Trial registration Retrospectively registered in ClinicalTrials.gov, the 13th of February with ID NCT06284616.